(untitled) (International relations and international law Journal, 2016)
The author highlights the need for a comprehensive scientific analysis of the dynamics of inter-ethnic marriages of Koreans in Uzbekistan and Kazakhstan in South Korea. On the development of cross-border marriages among ethnic Koreans is affected by one of the demographic characteristics, such as sex ratio in South Korea. One of the roots of the problem is seen as patriarchal attitudes of building family in Korea. Selective abortion of female fetuses has become a serious problem in Korea, especially with the advent of ultrasound examination of the fetus in the early 1980s. As a result, in 2000-th generation grows Korean nationals entering age, gender imbalance which has influenced an increase in inter-ethnic marriages with migrants, including from Central Asian countries.